PEMAHAMAN GURU DAN SISWA TENTANG MANAJEMEN BERBASIS SEKOLAH DI SMP NEGERI 8 PALANGKA RAYA - Sundari Sundari; Setiawan Setiawan (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2020)
This study aims to determine the understanding of teachers and students about school-based management in the State Junior High School 8 Palangka Raya. The study involved 56 teachers and 248 students as research samples. The technique of collecting data in this study is by spreading the questionnaire, interviews, and documenting the necessary data. Based on the results of the data analysis that has been done, it can be concluded that teachers and students at State Junior High School 8 Palangka Raya has had an understanding of school-based management which is proven by the answer of the questionnaire. Teacher understanding is in good category with a percentage yield of 71.63% and student understanding is in category enough with a percentage yield of 59.87%. In the future State Junior High School 8 Palangka Raya to make more efforts to improve the quality of teachers and students through workshops, trainings, and education seminars on school-based management, so that teachers and students better understand the understanding and implementation of school-based management, so that it is created a sense of having each other in school to improve the quality of education.